Synthesis of a specific processor from a high level programing languaje (ada) description - Deschamps, Jean-Pierre (1998)
Ada 95 is proposed as an alternative solution for describing digital embedded systems. Two examples are presented. The first one is a Program-state Machine; its translation to an Ada program is based on the use of concurrent tasks, entry calls, protected objects and asynchronous transfer of control (ATC). The second one is a specific processor connected to a serial channel and to a system bus.